Innovation management through knowledge and organizational socialization (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
This work aims to discuss the factors involved in the organizational socialization that contribute to the processes of creating knowledge and innovation at four food enterprises in the city of Marília – SP. The need of this study is clear from the point of view of the organizations’ human dimension, because it is considered that the inset of people into their labor, use and acceptation of the available technological tools, consciousness of cooperation and into other factors that build the environment, contribute either to execution of the activities or the construction of knowledge. Therefore, the psychological and behavioral aspects can make easier or hamper the innovation process, although it has being essential to the survival of the organizations, regarding the levels of competitiveness dictated by the current market. The research has a qualitative approach using the multiple study case in four food enterprises from the city of Marília/SP, each one of them of a size: micro, small, medium and large enterprise. The people of the research were the employees and the owners of the enterprises, who answered a semi-structured questionnaire, containing open and close questions, at their work place. The analysis of the results showed that in the innovation processes fulfilled by the enterprises there were difficulties in different natures, including those caused by low qualification of the work force when facing the new patterns of doing their activities. However, through the development of the socialization practices focused on the innovation that occurred, those difficulties were overcome and that allowed them to accomplish new procedures and to reach the expected results.Keywords: Organizational Socialization. Knowledge Management. Innovation Processes.Link para o texto completo (PDF)http://www.uel.br/revistas/uel/index.php/informacao/article/view/13901/pdf